Expansive Fixed Point Theorems for tri-simulation functions - Priya Shahi; Laxmi Rathour; Vishnu Narayan Mishra (The Journal of Engineering and Exact Sciences)
In this paper, we introduce the idea of -expansion by employing tri-simulation functions introduced by Gubran et al. [R. Gubran, W. M. Alfaqih and M. Imdad, Italian Journal of Pure and Applied Mathematics -N, 45 (2021) 419-430] in a metric space. Further, we shall use these mappings to study various fixed point results in complete metric spaces. The results of this paper generalize and improve several results on the topic in literature.